El futuro no está aquí. La expresión verbal de las emociones en los foros sobre Reproducción Asistida - Marimón Llorca , Carmen (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The physical and emotional challenges of assisted reproduction are depicted in particularly stark terms within the forums where patients exchange feelings and moods concerning their experiences of the process. The aim of this study is to analyse the emotional vocabulary contained in these discourses, paying particular attention to the lexical elements of the expression of emotions related to the projection of the future, which is where all actions and desires lead. The analysis is based on the concept of affect in Appraisal Theory (Martiny White 2005) and the conceptual maps of emotional vocabulary by Marina and López Penas (1999). Verbal processes and adjectival and nominal attributions are examined and distributed across the three evaluative axes of affect in order to also obtain critical access to the material. The analysis concludes that dissatisfaction and unhappiness predominate over any other sentiment. The corpus consists of testimonies collected in the NEOTERMED project.